13.3k views
3 votes
Solve the equation for L
k = 4L - 7

User Tkymtk
by
5.4k points

1 Answer

4 votes

Answer:


L = (k)/(4) + (7)/(4)

Explanation:

Isolate the variable, L. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

PEMDAS =

Parenthesis

Exponents (& Roots)

Multiplication

Division

Addition

Subtraction

~

First, add 7 to both sides of the equation:

k = 4L - 7

k (+7) = 4L - 7 (+7)

k + 7 = 4L

Next, divide 4 from both sides of the equation:

(k + 7)/4 = (4L)/4

L = (k + 7)/4

L = (k/4) + (7/4)


L = (k)/(4) + (7)/(4) is your answer.

~

User Bob Arnson
by
6.3k points